Bantayan Tourism Development Model Based on Community- Based Tourism to Strengthen the Sense of Belonging Among the Community - ., Harinawati; Hafni, Nur; Mardhiah, Anol (Journal of Ecohumanism, 2024)
This research raises the Bantayan Tourism Development Model Based on Community Based Tourism (CBT) for Strengthening the Sense of Belonging among the Community by measuring the Arnstein Participation Ladder. The research is motivated by the emergence of awareness of the younger generation in the development of tourism in Bantayan, Seunuddon sub-district by utilizing the existing potential of marine tourism, so that Bantayan becomes a tourist destination that is visited especially during the holiday season. By using the Community Based Tourism (CBT) Model, Empowerment Communication will see a sense of belonging among the Bantayan Community in tourism development, so that the Qualitative Research Method with a Qualitative Descriptive Approach. The results showed that the management of Bantayan beach tourism is dominated by people outside Bantayan due to limited capital in managing tourism, Bantayan people are involved in parking and security management. While BUMG Camar Laut is a supplier of goods to cafes along the Bantayan beach. The level of community participation in Bantayan tourism management is limited to parking management through parking contracts that are carried out every two weeks. Tourism awareness groups manage land leases and parking contracts. The allocation of income from land rent and parking is thirty percent for the tourism awareness group and seventy percent for the construction of the Mosque and Islamic boarding Schools. The Bantayan Community-based Tourism model is still not fully implemented, because the role of the community is still very minimal.